Pindolol decreases prolactin and growth hormone responses to intravenous L-tryptophan. - Smith, C; Ware, C; Cowen, P (1991)
The effects of pindolol on the prolactin (PRL) and growth hormone (GH) responses to intravenous tryptophan (LTP) were studied in eight healthy male volunteers. Pindolol pretreatment (40 mg over 48 h) markedly attenuated the GH response to LTP and modestly, but significantly, reduced the LTP-induced increase in plasma PRL. The disposition of LTP following infusion was not altered by pindolol. While the data are consistent with 5-HT1A receptor mediation of PRL and GH responses to LTP, the intrinsic sympathomimetic actions of pindolol might also be involved in the attenuation of the endocrine responses to LTP.